Elaboration of plasma-dielectric wakefield accelerator - Onishchenko, I.N.; Berezina, G.P.; Galaydych, K.V.; Kniazev, R.R.; Linnik, A.F.; Markov, P.I.; Omelaenko, O.L.; Pristupa, V.I.; Sotnikov, G.V.; Us, V.S. (Вопросы атомной науки и техники, 2016)
Theoretical and experimental investigations of the physical principles of wakefield accelerator based on the excitation
of accelerating wakefield in the plasma-dielectric structure by a long sequence of relativistic electron bunches
are presented. Enhancing the wakefield intensity is supposed to be achieved by using multibunch regime of excitation
for the coherent summation of wakefields of individual bunches and resonator regime for wakefields accumulation.
The acceleration of bunches in the total (plasma+dielectric) wakefields is realized by detuning of bunch repetition
frequency relatively to the frequency of the excited wakefield. In such a way the sequence of bunches is divided
into exciting and accelerated parts due to displacing latter part of bunches into accelerating phases of wakefield excited
by a former part of bunches of the same sequence. The influence of plasma in the transit channel on the amplitude
of excited plasma and dielectric wakefields and focusing exciting and accelerated bunches is investigated. Представлены теоретические и экспериментальные исследования физических принципов кильватерного
ускорителя, основанного на возбуждении ускоряющего кильватерного поля в плазменно-диэлектрической
структуре длинной последовательностью электронных сгустков. Увеличение амплитуды возбуждаемого
кильватерного поля достигается использованием мультибанчевого режима возбуждения для когерентного
сложения кильватерных полей отдельных сгустков и резонаторного режима для накопления кильватерных
полей. Ускорение сгустков в суммарном (плазменном+диэлектрическом) кильватерном поле реализовано
расстройкой частоты следования сгустков относительно частоты возбуждаемого кильватерного поля. Таким
путём последовательность сгустков разделяется на возбуждающую и ускоряемую части благодаря возника-
ющему смещению второй части сгустков в ускоряющие фазы кильватерного поля, возбуждённого первой
частью сгустков этой же последовательности. Исследовано влияние плазмы в пролётном канале на ампли-
туду возбуждаемых плазменного и диэлектрического кильватерных полей и фокусировку возбуждающих и
ускоряемых сгустков. Представлені теоретичні та експериментальні дослідження фізичних принципів кільватерного прискорюва-
ча, заснованого на збудженні прискорюючого кільватерного поля в плазмово-діелектричній структурі дов-
гою послідовністю електронних згустків. Збільшення амплітуди збуджуваного кільватерного поля досяга-
ється використанням мультибанчевого режиму збудження для когерентного складання кільватерних полів
окремих згустків і резонаторного режима для накопичення кільватерних полів. Прискорення згустків в су-
марному (плазмовому+діелектричному) кільватерному полі реалізовано розстройкою частоти слідування
згустків відносно частоти збуджуваного кільватерного поля. Таким шляхом послідовність згустків поділя-
ється на збуджуючу і прискорювану частини завдяки виникаючому зміщенню другої частини згустків в
прискорюючи фази кільватерного поля, збудженого першою частиною згустків цієї ж послідовності. Дослі-
джено вплив плазми в прольотному каналі на амплітуду збуджуваних плазмового та діелектричного кільва-
терних полів і фокусування збуджуючих і прискорюваних згустків.